NATIONAL QUALITY AWARDS (PART I) - García Pantigozo, Manud (1998)
Trends such as the long-term communications and TQM demonstrate that organizations stagnate, are overtaken by others. One way to be in training and competition while it is participating in the National Quality Awards, which are mostly an emulation of the Malcolm Baldrige Award - USA.